Transnational Solidarity in Times of Crises 2020
DOI: 10.1007/978-3-030-49659-3_2
|View full text |Cite
|
Sign up to set email alerts
|

Transnational Solidarity Organisations in Contemporary Greek Civil Society: Vibrant, Multifarious and Politicised

Abstract: Based on interviews conducted with groups working in the fields of migration, disabilities and unemployment, this chapter offers insights into Greek civil society as it has emerged and developed during the economic and refugee crises. The findings of these interviews also testify to a vibrant pre-crises Greek civil society, which has become even more multifarious and politicised. The newly imposed grievances as the backdrop of a deteriorating political framework led to the growth of the organisational field (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Almost all TSOs from Greece and Germany stated that they would pursue political objectives or perceive their help as a political statement. This also applies to those that address urgent needs, because of a strong interlinkage of providing support and political activism among the Greek and German TSOs (Kanellopoulos et al, 2021;Misbach, 2015;Schmid, 2019;Vathakou, 2015;Zamponi and Bosi, 2018). In comparison, only a few TSOs from Poland admitted to having any political motives or objectives (Petelczyc et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all TSOs from Greece and Germany stated that they would pursue political objectives or perceive their help as a political statement. This also applies to those that address urgent needs, because of a strong interlinkage of providing support and political activism among the Greek and German TSOs (Kanellopoulos et al, 2021;Misbach, 2015;Schmid, 2019;Vathakou, 2015;Zamponi and Bosi, 2018). In comparison, only a few TSOs from Poland admitted to having any political motives or objectives (Petelczyc et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the degree of the TSOs' politicisation can be related to distinct experiences with the impact of the economic and migration policy crises in the analysed countries (Kousis et al, 2020;Lahusen et al, 2020). In Greece, the harsh impact of the economic and so-called refugee crisis and the austerity policies led to an unprecedented emergence of grassroots solidarity initiatives (Kanellopoulos et al, 2021;Zamponi and Bosi, 2018). In a similar way, insufficient state responses to the arrival of high numbers of refugees and asylum seekers in 2015/2016 triggered a significant rise in grassroots TSOs in support of refugees in Germany (Speth and Becker, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Whether in the form of demand‐making to the Greek state, or criticising and trying to influence the policies of any given Greek government, or referring to internationalism and the need to overthrow capitalism, Greek TSOs are deeply concerned with and are active in politics. They are simultaneously concerned about the durability of European and national institutions, asking for economic and organisational support and legislative improvements (Kanellopoulos et al, 2021). As della Porta (2020) pointed out, in the context and aftermath of the crisis, ‘With the increasing competences of EU institutions, research on social movements and Europeanisation had indicated a move away from protest towards advocacy, understood as an adaptation of movements to EU structures’ (p. 227).…”
Section: The Greek Campaign Against Troika Memoranda and Austerity An...mentioning
confidence: 99%
“…An additional path of institutionalisation and Europeanisation is identified in TSOs in Greece, which are deeply concerned about maintaining ties to EU authorities, a network of transnational partners and civil society actors in meeting their goals, whilst being more likely to engage in EU partnerships, expressing the need to (a) construct and mobilise an active and critical citizenship across borders and (b) seek European funding, a more stable and reliable source of support (Kanellopoulos et al, 2021; Kousis et al, 2020).…”
Section: An Enduring Eu? the Idea Of Europe From The Street To The Po...mentioning
confidence: 99%
“…In keeping with the scholarship on counter-conduct and bottom-up governmentality, we identify those elements of inclusive experiments that can foster diverse cosmopolitan and egalitarian spaces. Moreover, it is important that civil society in the European South should not be understood as confined to formal charity, Nongovernmental Organisations (NGOs), or humanitarian assistance, but should rather be extended to include grassroots organisations, a variety of local solidarity initiatives and even transnational movements (Kanellopoulos et al, 2020;Kanellopoulos et al, 2021).…”
Section: Problematising Mobility Reception and Inclusionmentioning
confidence: 99%